Participatory Approaches to Agricultural Research and Extension Services - Sunil Kumar; Alok Kumar Srivastava; Milind D. Joshi; Mahesh Pathak; Vipin Kumar Misra; Dhirendra Kumar (Archives of Current Research International, 2024)
Participatory approaches in agricultural research and extension services have increasingly been recognized over recent decades as effective strategies for engaging farmers, integrating their expertise and preferences, and developing locally appropriate solutions. This article explores the various participatory methods used globally, particularly emphasizing practices in Asia and India. It traces the historical development of these approaches, outlines their core principles and methodologies, and presents evidence of their impact on agricultural productivity, sustainability, and the livelihoods of farmers. Through diverse case studies, including farmer field schools and participatory plant breeding, the article highlights the wide range of participatory techniques implemented in different regions. Additionally, it addresses the challenges and criticisms of participatory methods and suggests future directions for research and practice. Participatory approaches hold significant potential to enhance the responsiveness of agricultural research and extension services to the needs, knowledge, and creativity of farmers. Nonetheless, these approaches necessitate substantial investments in capacity building, institutional reforms, and policy adjustments to foster an environment conducive to participatory innovation. Continued research is crucial to evaluate the long-term effects and to facilitate the scaling up of successful participatory models.